“Virtuoso[S] Of Departure” - Sarah Bouttier (Sillages Critiques, 2018)
This paper reads three poems on absence in the light of current theories of the object, hoping to clarify various trends in contemporary poetry’s relation to absence. The three poems, “Meditations at Lagunitas” by Robert Hass (1979), “Silverfish, Moth” by Matthew Francis (2014), and “Pipistrelles” by Kathleen Jamie (2004) are extremely different in the functions and connotations they ascribe to absence. However, common trends emerge in the readings: the stronger the presence of a persona, the less space is allowed to absence in the poems; poems preoccupied with absence proceed by flashes, featuring being as “vibratory” in that it is mostly absent from our human perspective yet discloses itself to us intermittently; and finally, language seems at no point to be conceived as erasing the presence of its referee, or unable to refer to the ineffable: absence, in those poems, occurs in spite of words rather than because of them.